2023
DOI: 10.1111/acer.15046
|View full text |Cite
|
Sign up to set email alerts
|

Disrupted dynamic functional network connectivity in fetal alcohol spectrum disorders

Abstract: Background: Prenatal alcohol exposure (PAE) can result in harmful and long-lasting neurodevelopmental changes. Children with PAE or a fetal alcohol spectrum disorder (FASD) have decreased white matter volume and resting-state spectral power compared to typically developing controls (TDC) and impaired resting-state static functional connectivity. The impact of PAE on resting-state dynamic functional network connectivity (dFNC) is unknown. Methods: Using eyes-closed and eyes-open magnetoencephalography (MEG) res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 64 publications
1
1
0
Order By: Relevance
“…Studies in neuropsychiatric disorders with cognitive impairments have shown conflicting results on dynamic functional connectivity, with some studies showing decreased values for all global brain dynamic indices in schizophrenia, 24 autism, 52 some forms of major neurocognitive disorder 26 and in preterm born adolescents, 53 and others showing higher values for these metrics, including Alzheimer's disease 54 and other neonatal disorders such as foetal alcohol spectrum disorder. 55 Consistent with these studies, we found a subtle cognitive impairment indicated by inattention, hyperactivity and impulsivity scales in subjects at risk for CUD. To reconcile these findings, we can hypothesize that dynamic features could be related to the subject global cognitive functioning following an inverted-U model, so that subjects with low or high dynamic indices have impaired cognition, in the first case due to the lower possibility of configuring adaptive networks, while in the second, this is due to an instability in maintaining efficient and goal-oriented networks with frequent changes between distant states.…”
Section: Meta-state Changes In the Risk Of Cudsupporting
confidence: 89%
See 1 more Smart Citation
“…Studies in neuropsychiatric disorders with cognitive impairments have shown conflicting results on dynamic functional connectivity, with some studies showing decreased values for all global brain dynamic indices in schizophrenia, 24 autism, 52 some forms of major neurocognitive disorder 26 and in preterm born adolescents, 53 and others showing higher values for these metrics, including Alzheimer's disease 54 and other neonatal disorders such as foetal alcohol spectrum disorder. 55 Consistent with these studies, we found a subtle cognitive impairment indicated by inattention, hyperactivity and impulsivity scales in subjects at risk for CUD. To reconcile these findings, we can hypothesize that dynamic features could be related to the subject global cognitive functioning following an inverted-U model, so that subjects with low or high dynamic indices have impaired cognition, in the first case due to the lower possibility of configuring adaptive networks, while in the second, this is due to an instability in maintaining efficient and goal-oriented networks with frequent changes between distant states.…”
Section: Meta-state Changes In the Risk Of Cudsupporting
confidence: 89%
“…Studies in neuropsychiatric disorders with cognitive impairments have shown conflicting results on dynamic functional connectivity, with some studies showing decreased values for all global brain dynamic indices in schizophrenia, 24 autism, 52 some forms of major neurocognitive disorder 26 and in preterm born adolescents, 53 and others showing higher values for these metrics, including Alzheimer's disease 54 and other neonatal disorders such as foetal alcohol spectrum disorder. 55 …”
Section: Discussionmentioning
confidence: 99%